The Predictive Power of the Yield Curve across Countries and Time - Chinn, Menzie D.; Kucko, Kavan (My University, 2010)
This re-examination finds that power of the yield curve to predict economic activity has deteriorated in recent years. However, the authors find reason to believe that European country models perform better than non?European countries when using more recent data.